What was lost with IS-LM - Roger E. Backhouse; David Laidler (The University of Western Ontario, Department of Economics, 2003)
The dominance of the IS-LM model in macroeconomics after 1937 led to the neglect and sometimes the outright loss of a number of important issues that had earlier been prominent in the literature. All these losses were related to the fact that economic life takes place over time, from which the IS-LM model's formal comparative static nature abstracted. Ideas about explicit dynamic modelling, inter-temporal choice and expectations, the analysis of policy issues in terms of regimes, and coordination failures in the inter-temporal allocation of resources, are discussed from this standpoint. The extent and importance of the losses are discussed, as are questions about how the intellectual dominance of IS-LM affected the forms in which some of these ideas have subsequently re-emerged.
Keywords: 330